Performance improvements of interleaving VRMs with coupling inductors. - Pit-Leong Wong (IEEE Transactions on power electronics)
The multichannel interleaving buck converter with small inductance has proved to be suitable for voltage regulator modules (VRMs) with low voltages, high currents, and fast transients. Integrated magnetic components are used to reduce the size of the converter and improve efficiency. However, the structure of the integrated magnetic requires precise adjustment and is not mechanical stable. This paper proposes integrated coupling inductors between the channels to solve these problems. With the proper design, coupling inductors can improve both the steady-state and dynamic performances of VRMs with easier manufacturing